Formulasi dan Landasan Legalitas Teori Hajah dalam Hukum Islam Perspektif Ahmad Ibn ‘Abd al-Rahman Ibn Nasir al-Rashid - Aspandi; Muawanah (Tribakti: Jurnal Pemikiran Keislaman, 2021)
The formulation of the theory of hajah in Islamic law has basically gained a place as a methodology in the study of Islamic law. However, this theory of hajah has not received much response from Muslim thinkers and some are still questioning its legality basis. Specifically, this research outlines the formulation of Muslim thinkers' perspectives and their legality basis through library research. With a philosophical approach to the proposal of al-fiqh, this study describes the ideas, terminology, formulation and legality of hajah as one of the methodologies in Islamic law. This research yielded findings; Hujjahan hajah as the basis for the application of Islamic law relies on the sources and general arguments of the verses that show difficulties for everyone and beyond the capacity of the conditions in general. The formulation of hajah from the perspective of Muslim thinkers has various types based on their classification. This is because hajah is not only one kind or one kind.